Anticandidal Activity of Kalopanaxsaponin A: Effect on Proliferation, Cell Morphology, and Key Virulence Attributes of Candida albicans - Li, Ying; Shan, Mingzhu; Yan, Mingju; Yao, Huankai; Wang, Yuechen; Gu, Bing; Zhu, Zuobin; Li, Hongchun (Frontiers in Microbiology, 2019)
Background: The pathogenicity of Candida albicans is attributed to various virulence factors including adhesion to the surface of epithelial cells or mucosa, germ tube formation, hyphal morphogenesis, development of drug resistant biofilms, and so on. The objective of this study was to investigate the effects of Kalopanaxsaponin A (KPA) on the virulence of C. albicans. Methods: The effect of KPA on the virulence of C. albicans was characterized by an XTT reduction assay and fluorescent microscopic observation. The action mechanism was further explored using GC/MS system and BioTek Synergy2 spectrofluorophotometry. The cytotoxicity and therapeutic effect of KPA were were evaluated by the Caenorhabditis elegans-C. albicans infection model in vivo. Results: The minimum inhibitory concentration (MIC) of KPA was 8 16 μg/mL for various genotypes of C. albicans. The compound was identified as having remarkable effect on the adhesion, morphological transition and biofilm formation of C. albicans. The results of fluorescent microscopy and GC/MS system suggested that KPA could promote the secretion of farnesol by regulating the expression of Dpp3 and decrease the intracellular cAMP level, which together inhibited morphological transition and biofilm formation. Notably, KPA showed low toxicity in vivo and a low possibility of developing resistance. Conclusion: Our results demonstrated that KPA had remarkable efficacy against C. albicans pathogenicity, suggesting that it could be a potential option for the clinical treatment of candidiasis.